A People's Constitution: The Everyday Life of Law in the Indian Republic by Rohit De. Issue 2 (4th December 2020) - JOHN, Mathew
Abstract : This marvellous book by Rohit De flows from the meeting of two important aspects of Indian constitutional practice. First, the organization of the republic fashioned at independence as an instrument of socio-political change granting the state vast power over social, economic, and cultural activity. Second, a state organized to separate institutional powers and to protect individual freedom in order to check the runaway exercise of institutional power. In De's own words, the book is organised as a 'dialectic between the Indian Constitution as "politics of state desire" and the Constitution as "articulating insurgent orders of expectations from the state."' Set against these tensions in Indian constitutional practice, through a set of detailed ethnographies, De foregrounds citizen efforts to defend rights and freedoms that have operated to deepen constitutional culture in the early years of Indian independence.